BIM-BASED STEEL QUANTITY TAKE-OFF EVALUATION FOR STEEL FRAME BRIDGES: A COMPARISON BETWEEN AUTODESK REVIT AND CONVENTIONAL CALCULATIONS - Mutiara Ramadhanis; Gunawan; Roma Dearni (RADJA PUBLIKA, 2026)
Building Information Modeling (BIM) has become an effective approach for improving the efficiency and accuracy of quantity take-off (QTO) in construction projects, including steel truss bridges. This study evaluates the accuracy of steel weight quantity take-off generated using Autodesk Revit 2025 by comparing it with conventional calculations based on the Detail Engineering Design (DED). The comparison was conducted on 34 steel profile groups consisting of 210 structural members. Steel weight obtained from Autodesk Revit was compared with conventional calculations using percentage difference and statistical indicators, including Mean Error (ME), Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and the Coefficient of Determination (R²). The results show that Autodesk Revit produced a total steel weight of 27,526.57 kg, while the conventional calculation yielded 27,478.92 kg, resulting in a percentage difference of only 0.17%. The statistical evaluation produced an ME of 1.40 kg, an MAE of 9.31 kg, a MAPE of 1.89%, and an R² value of 0.9996, indicating excellent agreement between the two methods. Unlike previous studies that mainly compared total quantities, this study evaluates steel weight quantity take-off at the individual profile level, providing a more detailed assessment of Autodesk Revit accuracy for steel truss bridge structures. The findings demonstrate that Autodesk Revit 2025 is a reliable and effective tool for BIM-based steel quantity take-off.